Exploring Factors Associated With Complications Among Persons With Spinal Cord Injury Undergoing Surgical Closure of Stage 4 Pelvic Pressure Injuries - Teague, Laura; Browne, Gina; Jaglal, Susan; Calzavara, Andrew; Voth, Jennifer; Thabane, Lehana; Birch, Stephen; Campbell, Karen; McGillivray, Colleen; Deeb, Maya; et al. (Canadian Journal of Wound, Ostomy and Continence, 2026)
This study examined physiological and environmental variables associated with wound complications in persons with spinal cord injury (SCI) who underwent surgical repair of stage 4 pelvic pressure injuries (PI). A cohort of 88 patients undergoing 100 surgeries at one tertiary care hospital in Toronto, Canada, was identified. Patient-specific risk and operative variables were obtained from patient records and administrative data. Bivariate and Poisson regression analyses were used to model predictors of open versus closed wounds, 3 to 6 weeks following the surgical procedures. Eighty-eight patients having 100 surgical encounters were identified. Twenty-nine percent of the surgical encounters in females were open at 3 to 6 weeks postoperatively. Patients who had received more than 50 homecare nursing visits in the year before the index surgical date were less likely to have an open incision at the surgical follow-up clinic visit (incidence rate ratio [IRR] = 0.49; 95% confidence interval [CI] = 0.24, 0.99; p = 0.048). Patients who required surgical revision were more likely to have an open incision at the surgical follow-up clinic visit (IRR = 1.89; 95% CI = 1.15, 3.09; p = 0.01). Increased age, living in northern Ontario, and smoking were linked to a higher risk of open incision, though these findings were not statistically significant. Female gender and having peripheral vascular disease were identified as reducing the risk of having an open incision at the surgical follow-up clinic visit, but the findings were not statistically significant. Complication rates (incision open at routine surgical follow-up) were found to be 37% in this sample of SCI patients undergoing surgical closure of stage 4 PI. Future prospective studies to mitigate some of the risk factors are warranted.